Syura Dan Demokrasi Perspektif Hermeneutika Abdullah Saeed : Relevansinya Dengan Demokrasi Di Indonesia - Ananda Emiel Kamala; Anis Tilawati (Sophist : Jurnal Sosial Politik Kajian Islam dan Tafsir, 2020)
Abdullah Saeed offers a method of hermeneutics called the contextual approach. This approach is described in several works, one entitled Reading the Qur'an in the Twenty-First Century: A Contextualist Approach. The study in this article is one of the cases he once wrote in his book by applying the hermeneutic model, namely shura and democracy. The State of Indonesia is one of the Republican and democratic countries. The predominantly Muslim Indonesian population forms the country with the foundations of Islamic law, so the author is interested in studying the relevance of Indonesian democracy to the concept of shura in the Qur'an. The Indonesian democratic system in this article is examined from Abdullah Saeed's perspective on the concept of shura and democracy. In addition, the author also tries to identify Saeed's consistency in applying his contextual hermeneutic theory in this case. His findings are none other than that Saeed did not make the full interpretation in this case, so his conclusions still seem to rely on the pre-modern and modern interpretations he refers to, but he says the concept of shura has been contextualized as an attempt to equalize the democratic values ​​of a government country. As democracy in Indonesia has values ​​and ideas similar to the concept of shura in the Qur'an.